Banking and credit extension: does religious diversity matter?. Issue 12 (4th December 2017) - Ghosh, Saibal
Abstract : Purpose: While several facets of credit extension by banks have been extensively studied, one aspect which has largely bypassed the attention of researchers is the intrinsic attitude towards risk. To investigate this in detail the purpose of this paper is to employ data on India for an extended time period to understand whether religious diversity affects bank credit and other (flow) outcome variables, such as profitability, costs and returns. Design/methodology/approach: Given the longitudinal nature of the data, the author's employ fixed effects regression methodology which enables us to control for unobserved characteristics that might affect the dependent variable. Findings: The analysis indicates that religious diversity lowers credit off-take by lowering the number of accounts, although the number of deposit accounts improves. The behaviour however, differs across high- and low-income states and during the pre- and post-crisis periods. In addition, the evidence supports the fact that the overall negative credit response arises from the behaviour of national banks. Practical implications: The analysis explores an important and hitherto unidentified aspect driving banking outcomes in the Indian context. This would suggest that any policy intervention that seeks to influence bank behaviour would need to take on board the intrinsic risk-appetite of key stakeholders. Originality/value: To the best of the author's knowledge, this is one of the earliest studies for India to carefully examine the interface between religious diversity and bank behaviour.